Use of water-soluble microfertilizers for growing meteor table variety watermelon - E. A. Galichkina; S. M. Nadezhdkin; D. A. Makarenkov (Овощи России, 2023)
Relevance. In connection with the introduction of various types of chelated microfertilizers into production, it is necessary to develop new elements of varietal technology for the cultivation of melons and gourds in order to obtain stable yields in the arid conditions of the Volgograd Trans-Volga region. These studies will be relevant in this period of time.Material and technique. The object of research is watermelon, variety Meteor. We studied the types and methods of using chelate microfertilizers: Helaton Extra, Chelate B, Chelate Fe. Fertilizers were used for soaking seeds before sowing and for foliar treatment of plants during the growing season.Results. During the research period of 2019-2021, new forms of microfertilizers were studied. As a result of the research, new preparations for different methods of processing had a positive effect on the growth and development of table watermelon plants. The evaluation of the results obtained showed a positive effect of new microfertilizers on the germination energy and seed germination. The maximum growth of lashes was recorded when seeds were soaked before sowing: Helaton Extra preparation and foliar feeding of plants during the growing season with microfertilizer boron chelate. The best results of increasing the leaf surface were obtained in variants with the use of Helaton Extra microfertilizer for soaking seeds and treating plants on vegetative organs. Accordingly, the highest yield was obtained when using Helaton Extra fertilizer for seed treatment before sowing and spraying plants during the growing season. The output of marketable products was noted at a fairly high level. The average weight of the fetus in all studied variants ranged from 5.9 kg to 7.8 kg. The length of the growing season in all variants increased slightly. Comparative analysis of growth processes and productivity of watermelon variety Meteor when using new forms of water-soluble fertilizers for seed soaking and foliar treatment of plants showed greater efficiency from their use.